Penggunaan Citra Satelit untuk Kajian Perkembangan Kawasan Permukiman di Kota Semarang - Pigawati, Bitta; Rudiarto, Iwan (Forum Geografi, 2011)
This study aims to examine the development of settlement area in Semarang City using remote sensing imagery. This study used the spatial approach using quantitative descriptive analysis. Interpretation of satellite imagery is an initial activity of the stages of analysis. This activity aims to identify settlement area in the city, the analysis of developments in the residential area of Semarang will be done on the next step. The results showed that the settlement area in Semarang City was increased 9.78% from 1994 to 2005. Distribution of land settlement of the least extent in the sub district Gayamsari and Tugu. The largest residential area located in the sub-district Banyumanik, Tembalang and West Semarang. The regular, distribution is mostly located in Ngesrep Village, sub-district Banyumanik. On the other hand, the irregular distribution is located in Pudak Payung Village, sub-district Banyumanik and in the Rowosari Village, sub-district Tembalang. The composition of regular and irregular pattern were unchanged from 2006 to 2011. The evaluation result of the suitability of land use for settlement on the spatial plan (RTRW) all over the area indicated that more than 80% settlement areas were suitable with the plan.